PENGARUH KUALITAS DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SEPATU COMPASS DI JAKARTA BARAT - Wibisono, Diaz; Kramadibrata, Budi (Pusat Riset dan Inovasi Nasional, 2022)
The increasing interest in the fashion world today makes purchases of goods increase. This study aims to determine the effect of quality and brand image on purchasing decisions. Design/methodology/approach: This study used an associative quantitative approach with a sample size of 55 . The instruments used are questionnaires and tests. Testing the quality of the instrument includes validity and reliability tests. Data analysis used descriptive and correlation analysis, while for hypothesis testing using multiple linear regression analysis. Results: The results showed that there was a positive and significant relationship between quality and brand image on purchasing decisions with an R-Square value of 0.88. Research limitations/implications: This analysis is only conducted in the West Jakarta area and does not take into account other variables or moderating variables that influence purchasing decisions.